Analisis Kendala Dan Solusi Penanaman Pendidikan Karakter Bagi Guru Dalam Program PPK Di SMKS PGRI 7 Surabaya - Alfira Okta Mayangsari; Milla Uzlifatul Jannah; Ananda Aisyah Rachmawati; Syunu Trihantoyo (Transformasi: Journal of Economics and Business Management, 2023)
The purpose of this study is to provide details on how character education is developed in SMK PGRI 7 in Surabaya. Findings from this study shed light on the challenges faced by educators and the methods they used to overcome them in their quest to guide pupils toward more religious, empathetic, and patriotic conduct. Data for this study was gathered via interviews with teachers and administrators at SMK PGRI 7 Surabaya, observation of students and staff, and careful documenting of all relevant events. Methods such as observation, interviews, and documentation are used in data collecting. An interactive model is used for data analysis, which consists of many steps including data collecting, data reduction, data display, and conclusion drawing. The findings of this study point to several conclusions, including the following: (1) the development of educational technology affects the incorporation of character education; (2) parental involvement and encouragement positively affects the success of cultivating character education; (3) educators lend a hand in the form of concrete actions to ensure that students successfully implement character education; and (4) the existence of the new curriculum presents a minor barrier to educators' efforts to cultivate character education. The school has decided to address the problem of low teacher performance by funding their attendance at a series of seminars and training sessions focused on developing their "soft skills."